Desenvolvimento da educação em empreendedorismo no Brasil: um estudo de múltiplos casos - Sá, Eduardo Vimercati de (2019)
There is evidence that entrepreneurship education is the great impetus for the development of better professionals, not only in the creation of companies, but also as collaborators of these and even for personal life. The process of development of entrepreneurship education (EE) was researched in Brazilian higher education institutions (IES), considering their contributions to students and, consequently, to society. The general objective of this thesis is to identify and highlight the good practices carried out by such institutions; In this way, other higher education institutions in Brazil can initiate programs focused on entrepreneurship education. For this, the research was based on the qualitative approach, with studies of multiple cases, based on the recommendations of Eisenhardt (1989). Data were collected from in-depth semi-structured interviews and analyzed using the Atlas-ti qualitative analysis software. The data analysis was based on intracaso and intercaso analysis, whose objective is to compare the results to find similarities and differences and, thus, to validate the selected cases in the sampling procedure, which was characterized as theoretical and intentional. As a result of the research, it was verified that entrepreneurship education, developed in Brazilian higher education institutions, can serve as a reference for other institutions that wish to initiate and develop programs focused on this area of knowledge. The HEIs studied carry out various initiatives and programs focused on entrepreneurship education, disseminating entrepreneurial attitude and behavior in their students, teachers and collaborators. Enabling the individual development of those involved in this process, in addition to impacting the local community and, consequently, society. Finally, it is possible to affirm that the study on entrepreneurship education in Brazilian higher education institutions was very enriching, since it generated results that can be useful, contributing both in the aspect of its practice and in the field of future research on the subject, as well as for its development in other Brazilian educational institutions.